Can OP‐1 stimulate union in a rat model of pathological fracture post treatment for soft tissue sarcoma?. Issue 10 (25th June 2014) - Nicholls, Fred; Ng, Adeline H.; Hu, Sally; Janic, Katarina; Fallis, Cara; Willett, Thomas; Grynpas, Marc; Ferguson, Peter
ABSTRACT The goal of soft tissue sarcoma management in the extremities is limb preservation, often combining surgery and external beam radiation. In patients who have undergone this therapy in the thigh, pathologic fracture is a serious, late complication. Non‐union rates of 80–90% persist. No reliable biologic solution exists. A rat model combining one 18 Gy dose of radiation and diaphyseal periosteal excision reliably generates atrophic non‐union of femoral fractures. We hypothesized that augmentation with OP‐1 would increase union rate. Female Sprague‐Dawley retired breeder rats were randomized to Control, Disease (external beam radiotherapy and periosteal stripping), Control + OP‐1 (80 µg) and Disease + OP‐1 groups. Animals underwent prophylactic fixation and controlled left femur fracture. Twenty‐eight, 35, and 42 days post‐fracture were end‐points. Femora were analyzed using MicroCT, Back Scattered Electron Microscopy, and Histomorphometry. We observed a 2% union rate in the Disease groups (±OP‐1 treatment). The union rate in Control groups was 97%. MicroCT demonstrated a lack of callus volume in Disease groups. Heterotopic ossification was observed in some OP‐1 treated animals. The ineffectiveness of OP‐1 in stimulating fracture union in this model suggests the endogenous repair mechanism has been compromised beyond the capabilities of osteoinductive biologics. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1252–1263, 2014.